(untitled) (Research, Society and Development, 2021)
Teenage pregnancy is a widely discussed phenomenon in Brazil, and this debate is driven by the consequences of getting pregnant in this life cycle. Objective: To identify the sociodemographic and behavioral profile of pregnant adolescents from a low-lying suburb of Acre. Method: This is a cross-sectional study with a quantitative approach, carried out with 30 pregnant adolescents. Results: Most were 17 years old (40%), married (47%), brown skin color (50%), did not know how to inform family income (53%), incomplete high school (47%), did not have a paid job (97%), were evangelical (53%) and lived with a partner (53%). Most began sexual activity at age 15 (30%), and became pregnant for the first time at age 17 (23%). For the majority, the pregnancy was unplanned (73%) and they had 5 to 7 prenatal consultations (30%). All stated they have the support from the baby’s father (100%) and most received support from the family (94%). All continued their studies after pregnancy (100%), as this was the main life project they had before becoming pregnant (73%). The main change that occurred after pregnancy was the fact that they had to give priority to the baby (47%). Conclusion: Teenage pregnancy is associated with socio-economic, cultural and behavioral factors, highlighting the increasingly frequent need to implement effective measures to prevent and reduce risk behavior.